Experimental evaluation of the effect of supplementary nutrition and glutargine on regenerative properties - A.A. Kushta; S.M. Shuvalov (Medičnì Perspektivi)
The problem of alimentary dystrophy, which develops due to various reasons, is an urgent problem, especially in patients with tumors of the head and neck. After removal of tumors, patients have large postoperative defects that interfere with proper nutrition. Therefore, to provide the body with the necessary nutrients, enteral nutrition is especially important. In addition, successful wound healing requires adequate blood supply and sufficient levels of nutrients, which depends on the general condition of the body and the patient's diet. However, the degree of reparative processes correlates not only with the number of substrates of anabolism, but also with the proper functioning of the liver. The aim of our study was to investigate the effect of the drug for enteral nutrition and glutargin on the reparative properties of rats’ wounds on the background of partial food deprivation. The study was performed on 60 adult male rats weighing 280±20 grams of the Wistar line, with a mean age of 15 weeks. Prior to the experimental study the regenerative properties of the animals were on partial food deprivation. On the 10th day, a wound with a diameter of 2.0 cm was inflicted. Then the rats were divided into 4 groups: 1 group (control) received food according to physiological needs; Group 2 (food derivation (FD)); Group 3 (FD+enteral nutrition); Group 4 (FD+enteral nutrition +glutargin). Against the background of alimentary dystrophy (20% weight loss) on the first day there was a significant difference in the edges of the wound due to loss of its elasticity. Wound contraction processes up to 14-15 days in all observation groups were quite active, regardless of the factors of malnutrition with cereals or additional therapeutic diet "Peptamen" or in combination with glutargin. Thus, every three days the area of wounds decreased by 30-40 mm2 on an average. Only on the 15th-17th day the difference in the rate of wound contraction becomes visible and statistically significant. Thus, on the 15th day the largest wounds were in the second group on the background of partial food deprivation (p<0.05), at the same time in the first (control) and in the fourth groups the average area was almost equal (p>0.05). The smallest (p<0.05) area of wounds was observed in the first group (control) on the 15th day. On the 17th day wound healing was observed in the fourth group (FD+enteral nutrition+glutargin), despite the expansion of wounds on the first day. A pronounced therapeutic effect correcting alimentary dystrophy was obtained with enteral nutrition (Peptamen) and glutargin at a dose of 50 mg/kg, where the wounds healed simultaneously with those in the first (control) group, ie in animals with a normal diet, indicating a high effectiveness of the proposed method of correction of alimentary dystrophy. Enteral nutrition alone (Peptamen) was also effective, as evidenced by the small size of virtually epithelialized wounds on the 17th day.